Multinucleate Cell Angiohistiocytoma - Melícia, André (2020)
Multinucleated cell angiohistiocytoma (MCAH) is a rare clinical entity whose pathogenesis is not fully understood. It is more common in middle-aged women and is characterized by erythematoviolaceous papules or nodules, usually asymptomatic and predominantly located in the extremities. Histopathology is essential for making the diagnosis, consisting of typical alterations in the dermis, namely the proliferation of small vessels and the presence of multinucleated giant cells. Evolution is benign, although persistent, with few reported cases of spontaneous remission. We present the case of a 48-year-old man with MCAH, who exhibited asymptomatic papules and nodules grouped on the back of both hands, with a year of evolution. The diagnosis was made after histopathology, which excluded other differential diagnoses. With this case report, we intend to contribute to the knowledge about this entity and highlight the interconnection of clinical observation and histopathologic analysis.